Expansion of Cyclophyllidea Biodiversity in Rodents of Qinghai-Tibet Plateau and the “Out of Qinghai-Tibet Plateau” Hypothesis of Cyclophyllideans - Wu, Yao-Dong; Dai, Guo-Dong; Li, Li; Littlewood, D. Timothy J.; Ohiolei, John Asekhaen; Zhang, Lin-Sheng; Guo, Ai-Min; Wu, Yan-Tao; Ni, Xing-Wei; Shumuye, Nigus Abebe; Li, Wen-Hui; Zhang, Nian-Zhang; et al. (Frontiers in Microbiology, 2022)
The Cyclophyllidea comprises the most species-rich order of tapeworms (Platyhelminthes, Cestoda) and includes species with some of the most severe health impact on wildlife, livestock, and humans. We collected seven Cyclophyllidea specimens from rodents in Qinghai-Tibet Plateau (QTP) and its surrounding mountain systems, of which four specimens in QTP were unsequenced, representing “putative new species”. Their complete mitochondrial (mt) genomes were sequenced and annotated. Phylogenetic reconstruction of partial 28S rDNA, cox1 and nad1 datasets provided high bootstrap frequency support for the categorisation of three “putative new species”, assigning each respectively to the genera Mesocestoides, Paranoplocephala and Mosgovoyia, and revealing that some species and families in these three datasets, which contain 291 species from nine families, may require taxonomic revision. The partial 18S rDNA phylogeny of 29 species from Taeniidae provided high bootstrap frequency support for the categorisation of the “putative new species” in the genus Hydatigera. Combined with the current investigation, the other three known Taeniidae species found in this study were Taenia caixuepengi, T. crassiceps and Versteria mustelae and may be widely distributed in western China. Estimates of divergence time based on cox1+nad1 fragment and mt protein-coding genes (PCGs) showed that the differentiation rate of Cyclophyllidea species was strongly associated with the rate of change in the biogeographic scenarios, likely caused by the uplift of the QTP; i.e. species differentiation of Cyclophyllidea might be driven by host-parasite co-evolution caused by the uplift of QTP. We propose an “out of QTP” hypothesis for the radiation of these cyclophyllidean tapeworms.